Implications of Discriminative Regional Policies in Indonesia towards Women in Theperspective Feminist Legal Theory - Mondosiyoko, Hairu (Budapest International Research and Critics University, 2021)
In line with the state's obligation to promote the principle of non-discrimination and gender justice as stated in Article 2 of Law no. 7 of 1984 concerning the Ratification of the Convention on the Elimination of All Forms of Discrimination against Women and in line with Article 3 paragraph (3) of Law no. 39 of 1999 concerning Human Rights, Indonesia needs to close the door that opens the potential for discrimination against women in various aspects, including one of which is avoiding and eliminating discriminatory regional policies in Indonesia. Considering that there are still regional policies that have gaps in discrimination against vulnerable groups in general and women in particular. Currently, until 2016, Komnas Perempuan's research results show that there are 421 discriminatory policies at the provincial, district, and city levels. Regional policies in Indonesia that discriminate against women certainly have an impact on women, so it is necessary to make strategic efforts by the government against discriminatory regional policies.